Taxonomical remarks on Solenopsis laurentia (Campanulaceae) in Italy - Brullo, Salvatore; Brullo, Cristian; Cambria, Salvatore; Minissale, Pietro; Sciandrello, Saverio; Siracusa, Giuseppe; Tavilla, Gianmarco; Tomaselli, Valeria; Del Galdo, Gianpietro Giusso (Phytotaxa, 2023)
Based on herbarium and field investigations, the taxonomic status of Solenopsis laurentia (Campanulaceae), hygrophilous species belonging to the subfam. Lobelioideae showing a Mediterranean distribution is here examined. According to literature, it can be considered as a species complex, within which several taxa at specific and infraspecific rank were described. Morphological and nomenclatural studies carried out on several living populations coming from many Italian localities allowed to recognize five subspecies. For each of them, a detailed description, iconography, micromorphology of the seed testa and pollen grains, taxonomical relationships, chorology, conservation status and nomenclatural notes are provided. The recognized subspecies of Solenopsis laurentia are the following: a) subsp. laurentia, which is the most widespread in Italy and also in the Mediterranean area; b) subsp. gasparrinii (Tineo) comb. nov., which is quite common in Sicily with scattered occurrence in other Mediterranean localities; c) subsp. caespitosa Brullo, it seems currently localized in Apulia and Sardinia; d) subsp. parvula Brullo, occurring in some localities of the Italian peninsula, Sardinia and Tunisia; e) subsp. hyblaea, described as new for science from Sicily with a punctiform distribution.